1999
DOI: 10.1074/jbc.274.4.1873
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Phosphorylation in the Protein Kinase Cγ Knockout Mouse

Abstract: The phosphorylation state of three identified neuralspecific protein kinase C substrates (RC3, GAP-43/B-50, and MARCKS) was monitored in hippocampal slices of mice lacking the ␥-subtype of protein kinase C and wildtype controls by quantitative immunoprecipitation following 32 P i labeling. Depolarization with potassium, activation of glutamate receptors with glutamate, or direct stimulation of protein kinase C with a phorbol ester increased RC3 phosphorylation in wild-type animals but failed to affect RC3 phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…The phosphorylated Ng also stimulates the G-protein-coupled phosphoinositide second messenger pathways that trigger the mobilization of Ca 2ϩ from intracellular stores (8). PKC is the only known Ng kinase in vitro (5), and deletion of PKC ␥ gene in mice negates both the glutamate-and depolarization-mediated phosphorylation of Ng (9). The close functional relationship between Ng and PKC ␥ is further illustrated by their similar developmental expression patterns in the cerebral cortex (10)(11)(12).…”
mentioning
confidence: 87%
“…The phosphorylated Ng also stimulates the G-protein-coupled phosphoinositide second messenger pathways that trigger the mobilization of Ca 2ϩ from intracellular stores (8). PKC is the only known Ng kinase in vitro (5), and deletion of PKC ␥ gene in mice negates both the glutamate-and depolarization-mediated phosphorylation of Ng (9). The close functional relationship between Ng and PKC ␥ is further illustrated by their similar developmental expression patterns in the cerebral cortex (10)(11)(12).…”
mentioning
confidence: 87%
“…In vivo Ng phosphorylation in response to synaptic activation stimuli has been shown in several preparations such as brain slices (56,57) and cultured hippocampal neurons (58). Using PKCc knockout mice, it could be demonstrated that this PKC isoform is the only kinase involved in Ng phosphorylation upon high K 1 depolarization or glutamate receptor activation (59). Interestingly, Ng and PKCc show similar expression patterns during development and also share a highly coincident localization in the brain, both at the regional and the subcellular levels.…”
Section: Physicochemical Properties and Interactionsmentioning
confidence: 98%
“…In a way, this role could be considered as a ''memory effect,'' as occurs with CaMKII autophosphorylation, since it would prolong CaM availability and signaling in the postsynaptic space beyond the time window of the original stimulus. PKCc has been shown to be the isoform involved in the in vivo phosphorylation of Ng (59). Since PKCc needs Ca 21 and DAG for activation, only those stimuli capable to activate ionotropic and metabotropic receptors simultaneously could significantly increase Ng phosphorylation.…”
Section: Mechanisms and Functionmentioning
confidence: 99%
“…These proteins show sequence homology and have common biochemical characteristics. RC3 plays a role in Ca 2ϩ /calmodulin (Gerendasy et al, 1994a;Prichard et al, 1999) and protein kinase C signal transduction cascades (Baudier et al, 1991;Ramakers et al, 1999), and its phosphorylation is involved in long-term potentiation (Federov et al, 1995;Pasinelli et al, 1995;Chen et al, 1997;Ramakers et al, 1997) and long-term depression (De Graan et al, 1996). The expression level of RC3, but not its anatomical distribution, is under direct control of thyroid hormone at the transcriptional level (Morte et al, 1997;Martínez de Arrieta et al, 1999).…”
mentioning
confidence: 97%